Making America Great Again - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2019)
Trump has promised to `make America great again'. As a self-proclaimed expert on everything of import, he knows exactly how to increase domestic investment and consumption, boost exports, reduce the country's trade deficit, expand employment and bolster wages. And as America's leader-and-policymaker-in-chief, he has taken the necessary steps to achieve every one of these goals, or so he says. Capitalists and pundits follow him like imprinted ducks. His tweets rattle markets, his announcements are dissected by academics and his utterances are analysed to exhaustion by various media. A visiting alien might infer that he actually runs the world. And the alien wouldn't be alone. The earthly population too, conditioned by ivory-tower academics and popular opinion makers, tends to think of political figureheads as `leaders' and `policymakers'. Situated at the `commanding heights' of their respective nation states and international organizations, these `leaders' supposedly set the rules, make policies, steer their societies and determine the course of history. Or at least that's the belief. The reality, though, is quite different.
Keywords: E61; F13; F1; P16; F23; F51; D3; O24; 330; America's decline; capitalist mode of power; economic policy; Trump